2008
DOI: 10.1086/591857
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Surgical Site Infection (SSI) After Neurosurgery: Influence of the US or Brest (France) National Nosocomial Infection Surveillance Risk Index on SSI Rates

Abstract: A total of 5,628 neurosurgical patients were observed in France to assess the occurrence of surgical site infection (SSI). Their risk of SSI was defined by calculating both the US National Nosocomial Infection Surveillance and the Brest National Nosocomial Infection Surveillance risk indexes. This study compares SSI rates stratified according to either the US or Brest (France) National Nosocomial Infection Surveillance risk index. The SSI rates were correlated with National Nosocomial Infection Surveillance da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…SSIs can be classified into 3 types: superficial incisional infection, deep incisional infection, and organ/space infection. The incidence rate of SSI differs according to the type of surgery, and studies have reported that the incidence of SSI in colorectal cancer surgery is between 23% and 26% ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…SSIs can be classified into 3 types: superficial incisional infection, deep incisional infection, and organ/space infection. The incidence rate of SSI differs according to the type of surgery, and studies have reported that the incidence of SSI in colorectal cancer surgery is between 23% and 26% ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Âge, sexe masculin [14][15][16] ASA 2 [17] Diabète et glycémie préopératoire élevée [11] Alcoolisme [11] Insuffisance respiratoire en postopératoire [5,18] Présence d'une collection sous-galéale préopératoire [9] Facteurs de risque liés à la prise en charge d'une néoplasie intracrânienne active Radiothérapie préalable à la chirurgie [19] Chimiotherapie intraopératorie tel que l'implant de wafers de carmustine (Gliadel 1 ) [20] Facteurs de risque liés à la préparation du patient et à la période péri-opératoire Rasage [21,22] Asepsie cutanée [11,[23][24][25] Absence d'antibioprophylaxie [7] Dysfonction du drainage postopératoire [7] Drainage CSF (cerebrospinal fluid) [5] Facteurs de risque liés à l'acte chirurgical Type de chirurgie (implant, ouverture sinusale, fuite de LCR) [2,4,5,18,26] Ré-intervention, notamment dans le mois qui suit [2,27,28] Durée de l'intervention (notamment > 4 h) [2,[4][5][6]18] Chirurgie réalisée en urgence [2,18] Résection du muscle temporal (ce qui diminue la vascularisation locale) [18] Volume de perte de sang [11] Monitorage de la pression intracranienne > 5 jours [18,29,30] Facteurs de risque liés à la conservation du volet crânien lors d'une repose en 2 temps Cryoconservation …”
Section: Facteurs De Risque Liés Aux Patientsunclassified
“…Surgical site infection is divided into two categories by the US Centers for Disease Control and Prevention (CDC): superficial wound infection and deep organ/space infection, including anastomotic leak and abscess (1). The incidence of colorectal cancer surgery SSI was reported to be between 23% and 38% (2)(3)(4). Oncological and general outcomes were linked to surgical complications in colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%